SOCIAL AND CULTURAL ACTIVITIES WITH PEOPLE OF THE THIRD AGE TO OVERCOME THE SOCIAL EXCLUSION: A REGIONAL PERSPECTIVE - Elena V. Kharkovskaya; Elena V. Miroshnichenko; Galina N. Tutayeva (National Research Mordova State University, 2016)
Introduction: this paper discusses the specifics of socio-cultural activities with people of the third age to overcome the social exclusion, identifies reasons for the decline of alienation level in this category of citizens in conditions of activity of cultural institutions. Materials and Methods: the authors' findings are based on the philosophical, sociological, cultural, psychological and pedagogical literature and research methodology: observation, survey and content analysis. Results: the most effective methods of social and cultural activities in terms of overcoming the social exclusion of people of the third age were developed and experimentally tested. The main objective of the research was to examine the problems of exclusion among persons of the third age, as well as the possibilities of using social and cultural activities to overcome the social exclusion. In the paper the authors analyse the regional approach to the organisation of social and cultural activities of the elderly in institutions of social and cultural sphere. On the basis of the study the authors propose to extend and modify the variety of forms of leisure and intensify their use in working with people of the third age to overcome the social exclusion of an individual. All work on social and cultural activities with the elderly should be aimed primarily at optimising the social inclusion of elderly in society. Discussion and Conclusions: organisation of social and cultural activities for the elderly is a host of opportunities for the realisation of creative ideas. It is these new approaches to the activities of cultural institution's collective that help to enhance the interaction between cultural institutions employees and retirees. This study is not exhaustive and does not finalise the research into the role of social and cultural activities as a condition for overcoming the social exclusion of people of the third age. This topic needs further exploration.